Growth hormone, somatomedins and cancer risk - Jarosław Kozakowski; Piotr Dudek; Wojciech Zgliczyński (Wiedza Medyczna, 2020)
Growth hormone (GH) promotes growth and development in children and is the meaningful co-regulator of the metabolism in adulthood. GH may act directly, through its receptor (GHR), as well as via mediators – insulin-like growth factors: IGF-1, i.e. somatomedin C and IGF-2. Moreover, GH and two growth factors are involved in the mechanisms of cell proliferation, differentiation and survival, hence their oncogenic potential is propounded. Indeed, GH, somatomedins and their receptors are found abundantly in normal and cancer cells in several tissues. It has been shown in animal and human trials that polymorphisms and mutations that increase signal transmission from the GH and IGF-1 receptor are associated with more frequent tumors development and reduce life expectancy. Numerous epidemiological studies have confirmed a clear relationship between GH/IGF-1 level in circulation and a cancer-dependent morbidity and mortality. It dictates caution in case of treatment with use of growth hormone. Such replacement therapy is recommended in cases of GH deficiency. In the common opinion of scientific societies such treatment is generally safe, although in some cases unambiguous opinion in this field cannot be determined yet. On the other hand, on the basis of available evidence, GH cannot be recommended for use by the healthy elderly (ani-aging medicine), bearing in mind that GH decline with age may represent a beneficial adaptation to ageing. Understanding the molecular mechanisms by which GH and GH-dependent growth factors affect cell metabolism and proliferation will allow to use them in oncology in the future.